POLICY MODELLING FOR THE DEVELOPMENT OF UNMANNED AIRCRAFT SYSTEM INDUSTRY IN INDONESIA USING SYSTEM DYNAMICS METHOD - Ramadian, Aries Asrianto; Setiawan, Andri D. (The South African Journal of Industrial Engineering, 2024)
The unmanned aircraft system (UAS) industry in Indonesia is lagging behind in market share and innovation. An effective government policy is crucial to make domestic UAS products more innovative and competitive. However, still not enough academic research discusses the system structure of the UAS industry. Considering the complexity of the UAS industry, this study uses system dynamics in combination with a policy analysis framework to capture a broader perspective on the system. The conceptual model showed that a policy structure to shift customers from imported products to domestic products may help the development of the UAS industry and advance UAS technology.